Implementation of a Web-Based Educational Administration System to Enhance Accreditation at University - Sukmana, Nano; Hilman, Cecep; Darmawan, Eki Dudi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the implementation of a web-based educational administration system in improving accreditation performance at Telkom University. This research employed a qualitative approach using a case study design to gain an in-depth understanding of the phenomenon. The data were obtained from primary and secondary sources, including academic staff, administrative personnel, and accreditation teams. Data collection techniques consisted of in-depth interviews, direct system observations, and document analysis related to accreditation processes. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing to ensure systematic and valid findings. The findings indicate that the implementation of the web-based system significantly enhances data integration across units, accelerates administrative processes, improves data accuracy, and facilitates the preparation of accreditation documents in a more structured and efficient manner. In addition, the system strengthens coordination among stakeholders and improves institutional readiness in facing accreditation assessments. In conclusion, the implementation of a web-based educational administration system contributes substantially to administrative efficiency and plays a strategic role in improving accreditation outcomes. The significance of this study lies in providing empirical evidence and a practical model for higher education institutions in optimizing digital-based administrative systems to support sustainable accreditation quality improvement.